Қарақалпақ халқының батырлары минген тулпарлар ҳаққында (SCIENCE and SOCIETY, 2024)
The article describes the characteristics of the horses that the Karakalpak heroes rode, their loyalty, friendship and their place in the education of youth from a pedagogical point of view.